The effect of the oak powdery mildew, oak lace bug, and other foliofagous insects on the growth of young pedunculate oak trees - Marković, Čedomir; Kanjevac, Branko; Perišić, Uroš; Dobrosavljević, Jovan (Frontiers in Forests and Global Change, 2024)
Pedunculate oak (Quercus robur L., 1753) is one of the widely distributed oak species in Europe. A large number of organisms develop on its leaves. To determine the extent to which the oak powdery mildew, oak lace bug, and other foliofagous insects affect the growth of young oak trees, three experimental fields were selected in a 10-year-old pedunculate oak stand. In each of them, 50 trees were randomly selected, and their height was measured at the beginning of the vegetative season. The first experimental field was treated with a systemic insecticide, the second with a systemic fungicide, and the third, a comparison area, with water, during the entire vegetative season. At the end of the vegetative season, 25 plants with one apical branch were selected in each experimental field. Their height was measured, and 20 leaves were taken from each plant to determine the extent of the damage on them at the end of the experiment. After processing the obtained data, it was determined that: 1. Both foliofagous insects and oak leaf inhabiting fungi affect the growth of the oak trees significantly; 2. The oak lace bug did not influence the growth of the young trees significantly, as its abundance was low in all of the experimental areas; 3. The greatest damage on the leaves was caused by defoliator insects, which is why they contributed the most to the decrease in growth caused by insects; 4. The influence of the foliofagous insects on the growth of the trees was not significantly different from the influence of fungi; 5. Suppression of oak powdery mildew and foliofagous insects on young trees is useful as it positively influences the vitality and growth of those trees, and contributes to economic and ecological gain.